Extruded profile containing waste fan blade crushed material and preparation method thereof
By crushing, grinding and air-selecting and screening waste fan blade crushing materials, separating and combining raw materials in proportion for extrusion and granulation, the problems of unstable quality of wood-plastic composite materials and difficulty in recycling waste blades are solved, and pultruded profile production with high mechanical properties and cost advantages are achieved.
Patent Information
- Application Number
- CN202411966623.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
AI Technical Summary
The existing wood-plastic composite production process has problems such as poor compatibility of raw materials, intimate bonding, and unstable quality, which leads to the products being easily absorbed, expanded, cracked, and deformed; at the same time, waste wind power blades are difficult to recycle and reuse, causing environmental protection problems.
By crushing, grinding and air-selecting and screening the waste fan blade crushing material, thermoplastic foam, basa wood, resin/glass fiber and other components are separated, and a continuous double rotor mixer is added to the fixed component ratio for extrusion and granulation, and finally molding is performed using an extruder.
The mechanical properties of the pultruded profile containing waste fan blade crushing material is improved, production costs are reduced, the problem of handling wind turbine blades is solved, and the sustainable, environmentally friendly and efficient production of composite materials is achieved.
Smart Images

Figure BDA0005218512470000021 
Figure BDA0005218512470000051 
Figure FDA0005218512450000011
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite material recovery and reuse, and in particular to an extruded profile containing waste fan blade crushed material and a preparation method thereof. Background Art
[0002] The current production and processing technology of wood-plastic composite materials, such as molding and plastic extrusion, has problems such as poor compatibility between the filled wood fiber and the carrier plastic, loose bonding between the raw materials, and unstable quality of the products. This causes the products to easily absorb moisture and cause expansion, cracking, and deformation in actual applications.
[0003] The main raw materials of wood-plastic composite materials include plastics and wood fibers, and the fluctuation of the prices of these raw materials will directly affect the production cost and product pricing. Although some companies are exploring the use of low-cost raw materials (such as PCB circuit board powder instead of wood powder) to reduce production costs, the overall production cost of wood-plastic composite materials is still high, which limits the further expansion of its market.
[0004] As an important part of the wind power generation system, wind turbine blades have a complex material composition, mainly including reinforcing fibers (such as glass fiber GFRs), thermoplastics (such as polyethylene, polyurethane, polypropylene, polyvinyl chloride) and thermosetting resins (such as epoxy resin, vinyl ester, polyester). Due to the difficulty of remelting thermosetting composite materials, stable chemical properties, and long degradation time, discarded wind turbine blades have become the main recycling difficulty faced by the composite materials industry. Although landfill is the most common and cheapest treatment method, non-degradable materials that remain in the environment for a long time will pollute the soil, air and groundwater, posing a threat to human health. Therefore, due to the cross-linked structure of wind turbine blades and their difficulty in reprocessing or reuse, they have become the main recycling difficulty faced by the composite materials industry, and have increased the pressure to develop sustainable, environmentally friendly and efficient products.
[0005] At present, the difficulty in adding waste blade crushing materials into plastic products is that the crushing materials contain a lot of mixed components, including epoxy resin, fiber, structural adhesive, balsa wood, PVC foam / PET foam, etc. Since the blades are made of epoxy resin infusion, it is difficult to separate the components. If they are not separated, the properties of the components are different, which can easily lead to unstable production of composite materials. Summary of the invention
[0006] The object of the present invention is to provide an extruded profile containing waste fan blade crushed material and a preparation method thereof, so as to solve one or more of the above-mentioned prior art problems.
[0007] The method for preparing an extruded profile containing waste fan blade crushed material provided by the present invention comprises the following steps:
[0008] Step S1, breaking the discarded leaves into small pieces;
[0009] Step S2, adding the small pieces of crushed material into a grinding machine for grinding;
[0010] Step S3, using an air separation device to screen the thermoplastic foam, balsa wood, and resin / glass fiber;
[0011] Step S4, adding the fixed components into a continuous twin-rotor internal mixer, and extruding and granulating;
[0012] Step S5: using an extruder to extrude the particles.
[0013] In certain embodiments, the crushing diameter in step S1 is 1-3 cm.
[0014] In certain embodiments, the grinding mill in step S2 is a ball mill, and the grinding particle size is 40-600 mesh.
[0015] In certain embodiments, the air separation device in step S3 is a multi-stage cyclone separator, which controls the density screening interval by controlling the size of the gas introduced, and separates the three components of resin / glass fiber, balsa wood, and plastic foam through a three-stage linkage, and the plastic foam component is recycled and used separately.
[0016] In certain embodiments, the fixed components in step S4 are calculated by weight as follows:
[0017]
[0018] In certain embodiments, the polypropylene is PPH, and the melt index is 1-50g / 10min; the compatibilizer is PP-G-MAH, and the grafting rate is 1-5%, and the melt index is 1-100g / 10min; the lubricant is one or two of polyethylene wax, polypropylene wax, silicone powder, zinc stearate, lead stearate, calcium stearate, sodium stearate, magnesium stearate, and vinyl bisstearamide, and a mixture of two or more thereof; the antioxidant is a composite of an antioxidant and a light stabilizer, the antioxidant uses Extremely Easy 215, and the light stabilizer uses hindered amine light stabilizer 770, and the weight ratio of the antioxidant to the light stabilizer is 1:1.
[0019] In certain embodiments, the extruder in step S5 is a single-screw extruder or a twin-screw extruder; and the extrusion temperature is 190-250°C.
[0020] On the other hand, the extruded profile containing waste fan blade crushed material provided by the present invention is prepared by the following preparation method:
[0021] Step S1, breaking the discarded leaves into small pieces;
[0022] Step S2, adding the small pieces of crushed material into a grinding machine for grinding;
[0023] Step S3, using an air separation device to screen the thermoplastic foam, balsa wood, and resin / glass fiber;
[0024] Step S4, adding the fixed components into a continuous twin-rotor internal mixer, and extruding and granulating;
[0025] Step S5: using an extruder to extrude the particles.
[0026] Innovation:
[0027] 1. According to the density difference of different components, the raw material components are roughly separated by air separation;
[0028] 2. The coarse powder is re-weighed and added to ensure the consistency of the extruded profile.
[0029] Beneficial effect: The present invention improves the grinding process design and granulation composite formula, utilizes the density difference between different components, roughly separates the components in the blade crushed material, and then processes and granulates them according to the formula ratio, and then extrudes the profile. The obtained pultruded profile containing the waste wind turbine blade crushed material has higher mechanical properties and better cost advantages than the traditional wood-plastic composite profile, and can effectively solve the treatment of wind turbine blades. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below through embodiments.
[0031] Example 1
[0032] 1. Crushing of waste blades: Use a mechanical crusher to crush the collected waste fan blades into small pieces, ensuring that the diameter of the crushed blades is about 1.5 cm to ensure the efficiency and uniformity of the subsequent grinding process.
[0033] 2. Grinding: The broken blade pieces are added to the ball mill for grinding. The speed and ball size of the mill are optimized to obtain a powder with a particle size of 200 mesh. This particle size can not only ensure the uniformity of the powder, but also reduce the difficulty of subsequent processing.
[0034] 3. Wind screening: The ground mixture is screened by wind using a multi-stage cyclone separator. By adjusting the flow and pressure of the gas, the three main components of thermoplastic foam (PVC foam / PET foam), balsa wood, and resin / glass fiber are successfully separated. The plastic foam component is separated first due to its low density, collected separately and planned to be used in the production of other plastic products.
[0035] 4. Internal Mixing and Granulation: Add the screened components (by weight) into a continuous twin-rotor internal mixer according to the following formula for extrusion granulation:
[0036] 100 parts of polypropylene (PPH, brand ADXP770), melt index 45g / 10min;
[0037] Compatibilizer (PP-G-MAH) 20 parts, grafting rate 3%, melt index 70g / 10min;
[0038] Lubricant (mixture of polyethylene wax and silicone powder) 15 parts;
[0039] Anti-aging agent (mixed with 215 and 770 in a ratio of 1:1) 3 parts;
[0040] Resin / glass fiber powder 100 parts;
[0041] 100 parts of balsa wood powder;
[0042] The temperature of the internal mixer is controlled at 200°C to ensure that the components are fully mixed and melted, and then granulated through the extruder head.
[0043] 5. Extrusion molding: Use a twin-screw extruder to extrude the granulated particles. The temperature of the extruder is controlled at 220°C to ensure that the material maintains proper fluidity during the extrusion process. Pultruded profiles with a stable cross-sectional shape are obtained through die extrusion.
[0044] Example 2
[0045] The following adjustments are made to the formula based on Example 1:
[0046] 100 parts of polypropylene (PPH, model X30G), melt index of 10g / 10min;
[0047] Compatibilizer (PP-G-MAH) 10 parts, grafting rate 3%, melt index 50g / 10min;
[0048] Lubricant (vinyl bisstearamide) 3 parts;
[0049] 2 parts of antioxidant (mixed with 215 and 770 in a ratio of 1:1);
[0050] Resin / glass fiber powder 60 parts;
[0051] 40 parts of balsa wood powder.
[0052] Comparative Example 1
[0053] In order to evaluate the effect of the compatibilizer on the performance of the composite material, the amount of the compatibilizer (PP-G-MAH) was reduced to 5 parts (i.e., the minimum value in the formula) in this comparative example based on Example 1. The other steps and parameters remained unchanged.
[0054] Comparative Example 2
[0055] In order to evaluate the effect of lubricant on the processing performance of the composite material, this comparative example reduced the amount of lubricant (polyethylene wax and silicone powder mixture) to 1 part (i.e., the minimum value in the formula) based on Example 1. Other steps and parameters remained unchanged.
[0056] Comparative Example 3
[0057] In order to evaluate the effect of the ratio of resin / glass fiber powder and balsa wood powder on the mechanical properties of the composite material, this comparative example is based on Example 1, and the resin / glass fiber powder, balsa wood, and plastic foam powder are mixed in an amount of 100 parts without distinction. Other steps and parameters remain unchanged.
[0058]
[0059] Results Analysis
[0060] By analyzing the experimental results of Example 1, Example 2 and Comparative Example 1, Comparative Example 2 and Comparative Example 3, the following conclusions can be drawn:
[0061] 1. Effect of compatibilizer (Comparison between Comparative Example 1 and Example 1)
[0062] Tensile strength: The tensile strength of Example 1 is 52.1 MPa, while the tensile strength of Comparative Example 1 is 41.2 MPa, which is reduced by about 10.9 MPa.
[0063] Elongation at break: The elongation at break of Example 1 is 1.05%, while the elongation at break of Comparative Example 1 is 0.58%, which is reduced by about 0.47 percentage points.
[0064] Simple supported beam unnotched impact strength: The impact strength of Example 1 is 1.03KJ / M 2 , while the impact strength of comparative example 1 is 0.56KJ / M 2 , reduced by about 0.47KJ / M 2 .
[0065] Conclusion: Increasing the amount of compatibilizer (PP-G-MAH) can significantly improve the tensile strength, elongation at break and impact strength of the composites, indicating that the compatibilizer plays an important role in improving the compatibility between the components.
[0066] 2. Effect of lubricant (Comparative Example 2 vs. Example 1):
[0067] Tensile strength: The tensile strength of Example 1 is 52.1 MPa, while the tensile strength of Comparative Example 2 is 46.5 MPa, which is reduced by about 5.6 MPa.
[0068] Elongation at break: The elongation at break of Example 1 is 1.05%, while the elongation at break of Comparative Example 2 is 0.92%, which is reduced by about 0.13 percentage points.
[0069] Simple supported beam unnotched impact strength: The impact strength of Example 1 is 1.03KJ / M 2 , while the impact strength of comparative example 2 is 0.98KJ / M 2 , reduced by about 0.05KJ / M 2 .
[0070] Conclusion: Increasing the amount of lubricant (polyethylene wax and silicone powder mixture) can improve the tensile strength, elongation at break and impact strength of the composite material, but the effect is relatively small. Lubricants mainly improve fluidity during processing, reduce friction resistance and improve production efficiency.
[0071] 3. Effect of the ratio of resin / glass fiber powder and balsa wood powder (Comparative Example 3 vs. Example 1):
[0072] Tensile strength: Comparative Example 3 cannot provide accurate tensile strength data due to uneven mixing of components and inability to stably form.
[0073] Elongation at break and impact strength: Similarly, Comparative Example 3 also fails to provide accurate elongation at break and impact strength data.
[0074] Conclusion: Indiscriminate mixing of resin / glass fiber powder, balsa wood powder and plastic foam powder will lead to uneven composite material components, affect the mechanical properties and processing properties of the material, and make stable molding impossible.
[0075] 4. Comparison between Example 1 and Example 2:
[0076] Tensile strength: The tensile strength of Example 1 is 52.1 MPa, while the tensile strength of Example 2 is 43 MPa, which is reduced by about 9.1 MPa.
[0077] Elongation at break: The elongation at break of Example 1 is 1.05%, while the elongation at break of Example 2 is 1.53%, an increase of about 0.48 percentage points.
[0078] Simple supported beam unnotched impact strength: The impact strength of Example 1 is 1.03KJ / M 2 , while the impact strength of Example 2 is 1.56KJ / M 2 , increased by about 0.53KJ / M 2 .
[0079] Conclusion: The tensile strength of Example 1 is higher, while the elongation at break and impact strength of Example 2 are higher. This may be due to the reduced amount of resin / glass fiber powder and balsa wood powder in Example 2, which makes the material softer but reduces the tensile strength. The specific formula should be adjusted according to the actual application requirements.
[0080] In summary, by optimizing the amount of compatibilizer, lubricant, and the ratio of resin / glass fiber powder and balsa wood powder, the mechanical properties of the pultruded profile containing waste fan blade crushed material can be significantly improved. At the same time, the raw material components are roughly separated by an air separation device, which can effectively ensure the product consistency of the extruded profile. The technical solution of the present invention provides a new way for the recycling and reuse of waste fan blades, and has broad application prospects.
[0081] The above description is only a preferred embodiment of the present invention. It should be pointed out that, for ordinary technicians in this field, several modifications and improvements can be made without departing from the creative concept of the present invention, and these should also be regarded as within the scope of protection of the invention.
Claims
1. A method for preparing an extruded profile containing waste fan blade crushed material, characterized in that: The following steps are involved: Step S1, breaking the discarded leaves into small pieces; Step S2, adding the small pieces of crushed material into a grinding machine for grinding; Step S3, using an air separation device to screen the thermoplastic foam, balsa wood, and resin / glass fiber; Step S4, adding the fixed components into a continuous twin-rotor internal mixer, and extruding and granulating; Step S5: using an extruder to extrude the particles.
2. The method for preparing an extruded profile containing waste fan blade crushed material according to claim 1, characterized in that: The crushing diameter in step S1 is 1-3 cm.
3. The method for preparing an extruded profile containing waste fan blade crushed material according to claim 1, characterized in that: In step S2, the grinding machine is a ball mill, and the grinding particle size is 40-600 mesh.
4. The method for preparing an extruded profile containing waste fan blade crushed material according to claim 1, characterized in that: The air separation device in step S3 is a multi-stage cyclone separator, which controls the density screening interval by controlling the size of the gas introduced, and separates the three components of resin / glass fiber, balsa wood, and plastic foam through three-stage linkage, and the plastic foam component is recycled and used separately.
5. The method for preparing an extruded profile containing waste fan blade crushed material according to claim 1, characterized in that: The fixed components in step S4 are calculated by weight:
6. The method for preparing an extruded profile containing waste fan blade crushed material according to claim 5, characterized in that: The polypropylene is PPH, and its melt index is 1-50g / 10min; the compatibilizer is PP-G-MAH, and its grafting rate is 1-5% and its melt index is 1-100g / 10min; the lubricant is one or two of polyethylene wax, polypropylene wax, silicone powder, zinc stearate, lead stearate, calcium stearate, sodium stearate, magnesium stearate, and vinyl bisstearamide, and a mixture of two or more thereof; the antioxidant is a composite of an antioxidant and a light stabilizer, the antioxidant is Extremely Easy 215, and the light stabilizer is hindered amine light stabilizer 770, and the weight ratio of the antioxidant to the light stabilizer is 1:
1.
7. The method for preparing an extruded profile containing waste fan blade crushed material according to claim 1, characterized in that: The extruder in step S5 is a single-screw extruder or a twin-screw extruder; the extrusion temperature is 190-250°C.
8. An extruded profile containing waste fan blade crushed material obtained by the preparation method according to any one of claims 1 to 7.